TEACHER STRATEGIES IN IMPLEMENTING INTERACTIVE LEARNING MEDIA IN INDONESIAN LANGUAGE SUBJECTS FOR GRADE IV UNDER THE MERDEKA CURRICULUM IN ELEMENTARY SCHOOLS - Umar, Nur Fadilatin; Sukartono, Sukartono (Jurnal Pendidikan (Teori dan Praktik), 2025)
This study aims to analyze the teacher's strategy in applying interactive learning media in class IV Indonesian language subjects of Merdeka Curriculum at  Elementary School. The method used is descriptive qualitative with data collection techniques through interviews, observation, and documentation. Data validity through source triangulation and technique triangulation, which ensures consistency and accuracy of data from various perspectives. The collected data were analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results show that the use of interactive learning media such as Wordwall and animated videos is effective in improving students' skills, including speaking, reading, listening and writing. It also creates a learningatmosphere that is fun, participatory, and relevant to students' needs. However, some obstacles were found, such as limited technology facilities, inadequate projectors, and unstable internet access. Proposed solutions include improving school facilities and improving internet access. This research confirms that interactive learning media is a relevant innovation to support Merdeka Curriculum, provide an engaging learning experience, and significantly improve student learning outcomes.